2015
DOI: 10.18831/james.in/2015031005
|View full text |Cite
|
Sign up to set email alerts
|

Design to Replace Steel Drive Shaft in Automobiles with Hybrid Aluminium Metal Matrix Composite

Abstract: Many research works have been carried out in automobile industry to optimize the weight of the vehicle, as weight has a significant influence on fuel consumption. It is vital that weight optimization process should be carried out without compromising the dynamic behaviours of the components and its functions. In this paper an attempt has been made to check the suitability of hollow drive shaft (propeller drive shaft) by varying the internal diameter of the shaft. Models were created by varying the internal dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…It was found that MgO possesses better mechanical property than the other reinforcements. A lot of researchers had 9 concentrated on developing new composites such as Al 6061, LM25 reinforcing with various elements such as TiB 2 , SiC, TiC, ZrB 2 , AIN, Si 3 N 4 , Al 2 O 3 and their mechanical properties were analyzed by earlier researchers [6][7][8][9][10][11][12][13][14][15][16]. Very few works were identified in analyzing the effect of MgO on hardness analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that MgO possesses better mechanical property than the other reinforcements. A lot of researchers had 9 concentrated on developing new composites such as Al 6061, LM25 reinforcing with various elements such as TiB 2 , SiC, TiC, ZrB 2 , AIN, Si 3 N 4 , Al 2 O 3 and their mechanical properties were analyzed by earlier researchers [6][7][8][9][10][11][12][13][14][15][16]. Very few works were identified in analyzing the effect of MgO on hardness analysis.…”
Section: Introductionmentioning
confidence: 99%